Tunable ultra-broadband terahertz metamaterial absorber based on vanadium dioxide strips. Issue 18 (17th April 2023) - Gevorgyan, Lilit; Haroyan, Hovhannes; Parsamyan, Henrik; Nerkararyan, Khachatur
Abstract : A simple design of a tunable ultra-broadband metamaterial absorber of terahertz (THz) radiation based on vanadium dioxide (VO2 ) configurations is proposed, having wide incidence angle tolerance and polarization insensitivity. Abstract : A simple design of an ultra-broadband metamaterial absorber (MMA) of terahertz (THz) radiation based on vanadium dioxide (VO2 ) configurations is proposed. The system is composed of a top pattern representing orderly distributed VO2 strips, a dielectric spacer and an Au reflector. Theoretical analysis based on the electric dipole approximation is performed to characterize the absorption and scattering properties of an individual VO2 strip. The results then are used to design an MMA composed of such configurations. It is shown that the efficient absorption characteristics of the Au–insulator–VO2 metamaterial structure can be ensured in a broad spectrum of 0.66–1.84 THz with an absorption band relative to the center frequency reaching as high as 94.4%. The spectrum of the efficient absorption can be easily tuned via the corresponding choice of strip dimensions. Wide polarization and incidence angle tolerance for both transverse electric (TE) and transverse magnetic (TM) polarizations are ensured by adding an identical parallel layer rotated by 90 degrees in respect to the first one. Interference theory is applied to elucidate the absorption mechanism of the structure. The possibility of modulation of the electromagnetic response of MMA relying on the tunable THz optical properties of VO2 is demonstrated.